Spiny Projection Neuron Dynamics in Toxin and Transgenic Models of Parkinson’s Disease - Du, Yijuan; Graves, Steven M. (Frontiers in Neural Circuits, 2019)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder that results from the progressive degeneration of substantia nigra pars compacta (SNc) dopamine (DA) neurons. As a consequence of SNc degeneration, the striatum undergoes DA depletion causing the emergence of motor symptoms such as resting tremor, bradykinesia, postural instability and rigidity. The primary cell type in the striatum is the spiny projection neuron (SPN), which can be divided into two subpopulations, the direct and indirect pathway; the direct pathway innervates the substantia nigra pars reticulata and internal segment of the globus pallidus whereas the indirect pathway innervates the external segment of the globus pallidus. Proper control of movement requires a delicate balance between the two pathways; in PD dysfunction occurs in both cell types and impairments in synaptic plasticity are found in transgenic and toxin rodent models of PD. However, it is difficult to ascertain how the striatum adapts during different stages of PD, particularly during premotor stages. In the natural evolution of PD, patients experience years of degeneration before motor symptoms arise. To model premotor PD, partial lesion rodents and transgenic mice demonstrating progressive nigral degeneration have been and will continue to be assets to the field. Although, rodent models emulating premotor PD are not fully asymptomatic; modest reductions in striatal DA result in cognitive impairments. This review gives a brief summary of SPN dynamics in animal models of PD.